PTU-096 The uptake of pharmacy-based targeted screening for hepatitis c in an isolated network of people who inject drugs. (17th June 2017) - Buchanan, R; Parkes, J; Noble, K; Grellier, L; Youde, R; Khakoo, SI
Abstract : Introduction: Hepatitis C (HCV) is increasingly easy to treat but barriers to care remain including undiagnosed cases of infection in people who inject drugs (PWID) 1 . The objective of this study was to assess the uptake of pharmacy based dry blood spot (DBS) testing within a population of PWID living in a geographically isolated community on the Isle of Wight, UK (IOW). Method: Twenty-two pharmacies on the IOW were enrolled to offer free dry-blood spot testing to those at risk of HCV. After 24 months the program was evaluated, PWID living on the IOW were recruited to a validated behavioural and social network survey via respondent driven sampling (RDS) 2 – a cross-sectional sampling technique designed for use in hidden populations. Population estimates were calculated using RDSanalyst and network measures were calculated using UCInet. Results: In 24 months, twenty community pharmacies conducted 186 tests, which included 68 individuals who disclosed a primary risk factor of injecting drug use. Recruitment to the survey took a further 3 months, passed through 12 waves and enrolled 69 eligible participants including 5 seeds . The mean age of the sample was 39 years, the majority injected heroin (86%) and had injected in the last 30 days (57%). Seventeen (25%) of the survey participants were positive for HCV RNA. Twenty-three (33%) of the survey sample had reported undergoing a DBS test in a community pharmacy giving an estimated 'population proportion' of 36% (95% confidence intervals 19%–55%). There was no significant association between pharmacy based testing and social network position (in - degree centrality) (p=0.5) but there was a significant association with drug support centre attendance (p=0.02) and resident area (p=0.02). Conclusion: Community pharmacies have the potential to be an effective venue for serial HCV testing in PWID but efforts need to be made to reach those living in remote areas without access to a testing pharmacy and those not already engaged with drug support services. References: . Public Health England. Hepatitis C in the UK . [Online] 2014. Available from: https://www.gov.uk/government/publications/hepatitis-c-in-the-uk [Accessed Sept 20th 2015]. . Heckathorn D. Respondent-driven sampling: A new approach to the study of hidden populations1997;44(2):174–199. Disclosure of Interest: None Declared